2017
DOI: 10.7705/biomedica.v38i0.3683
|View full text |Cite
|
Sign up to set email alerts
|

Vitamina D y riesgo de preeclampsia: revisión sistemática y metaanálisis

Abstract: The inverse association we found suggests that the higher the levels of vitamin D the lesser the probability of developing preeclampsia, in spite of the heterogeneity of the global measurement in this type of analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 57 publications
1
14
0
8
Order By: Relevance
“…It is hypothesized that the role vitamin D plays in modulating immune function and preventing inflammation is the likely mechanism for which vitamin D supplementation in protecting maternal and fetal health [15]. Wagner et al have demonstrated that an intake of 4000 IU/d during pregnancy, to achieve a serum 25(OH)D above 40 ng/mL (100 nmol/L), can reduce the incidence of preterm by more than half [16] and may reduce other complications of pregnancy including preeclampsia, gestational diabetes and possibly post-partum hemorrhage [17][18][19]. Their findings have resulted in a vitamin D supplementation program (in place since 2017), wherein 5000 IU/d of vitamin D is provided to all pregnant women, implemented at five hospitals within the Medical University of South Carolina [20].…”
Section: Vitamin D and Pregnancymentioning
confidence: 99%
“…It is hypothesized that the role vitamin D plays in modulating immune function and preventing inflammation is the likely mechanism for which vitamin D supplementation in protecting maternal and fetal health [15]. Wagner et al have demonstrated that an intake of 4000 IU/d during pregnancy, to achieve a serum 25(OH)D above 40 ng/mL (100 nmol/L), can reduce the incidence of preterm by more than half [16] and may reduce other complications of pregnancy including preeclampsia, gestational diabetes and possibly post-partum hemorrhage [17][18][19]. Their findings have resulted in a vitamin D supplementation program (in place since 2017), wherein 5000 IU/d of vitamin D is provided to all pregnant women, implemented at five hospitals within the Medical University of South Carolina [20].…”
Section: Vitamin D and Pregnancymentioning
confidence: 99%
“…However, the scientific community is recently moving towards the recognition of the importance of vitamin D deficiency in the development of these pathological conditions [28]. Indeed, recent meta-analyses of observational studies highlighted the existence of an inverse ratio between vitamin D levels and the development of PE as well as GH, and provided evidence for an increased risk of gestational hypertensive disorders at vitamin D concentrations <20 ng/ml (<50 nmol/L) [12,28,29]. Vitamin D concentrations <12 ng/mL (<30 nmol/L) in early pregnancy have been associated with a higher risk for PE in comparison to concentrations >20 ng/mL (>50 nmol/L) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Among preeclampsia targets, AR and VDR were always selected among the top 5 targets in all clusters. Progesterone and estrogen receptors are known to be involved in preeclampsia pathogenesis [25] and vitamin D is considered as an effective preventive treatment [5,26]. Similarly, ESR1, ESR2, CHRM4 and CHRM3 were also regularly highly ranked in the four clusters.…”
Section: Models and Early Recognition Abilitymentioning
confidence: 99%
“…Any drug for the treatment of preeclampsia will have, in general, two possible options (which are not necessarily independent of each other): (1) to be a preventive drug for use early in pregnancy to prevent a possible preeclampsia manifestation or (2) to be a drug capable of handling symptoms and/or disease progression. The first option includes the use of low-dose aspirin in women with high risk of preeclampsia [2], the use of magnesium sulfate [3] and the administration of vitamin D [4,5]. Drugs in the latter group could extend the gestational age, thus increasing the chances of fetal growth and maturity to facilitate a safer delivery.…”
Section: Introductionmentioning
confidence: 99%